Sea level response to late Pliocene-Quaternary erosion and deposition in Scandinavia. (1st February 2023) - Jungdal-Olesen, G.; Pedersen, V.K.; Andersen, J.L.; Gomez, N.; Mitrovica, J.X.
Abstract: Erosion and deposition can perturb regional sea level significantly by altering the Earth's surface and by redistributing mass. However, no studies have investigated the importance of these geomorphic processes for glacial settings on glacial-interglacial time scales, despite large erosion rates and the inherent importance of sea-level changes for ice-sheet dynamics and stability. Here we quantify how glacial erosion and depositional processes have affected relative sea level in western Scandinavia where glacial activity has reoccured periodically throughout the late Pliocene-Quaternary. By comparing offshore sediment volumes with onshore topographic relief, we quantify erosion and deposition for the last two glacial cycles as well as the entire late Pliocene-Quaternary. Specifically, we develop a history of erosion and deposition for the last two glacial cycles by scaling the erosion rate with the normalised global ice volume through time. We use the ice model ICE6G_C as a global ice history and calculate sea-level changes through time as a result of ice, water, and sediment loading using a global gravitationally self-consistent sea-level model. Our results show that geomorphic mass redistribution, excluding direct changes in ocean depth owing to erosion and deposition, has caused a sea-level fall of ≈50–100 m along the southern coast of Norway during the last two glacial cycles reaching ≈120 m in the offshore Skagerak region. During the late Pliocene-Quaternary, the total sea-level fall reach as much as ≈ 310 m in Skagerak. These results showcase the importance of erosion and deposition for the relative sea-level history of Scandinavia with implications for studies of ice-sheet history and regional glacial rebound in this region and elsewhere. Highlights: We investigate the effect of erosion and deposition on sea-level in Scandi-navia. Erosion in the last two glacial cycles causes a maximum sea-level fall of >120 m. Erosion may explain signals recorded in sea-level data from the Eemian.